Educational Robotics: Building and Applying an App-controlled Car to Study Newton's Laws - Matos Maicon Teixeira; Zannin Marcelo (De Gruyter, 2021)
The use of technology - including mobile phones - in classrooms is a growing and promising trend, but it still needs research on ways to integrate it in classrooms and on its impacts. We propose a low cost educational product where students assemble an Arduino car remotely controlled through a mobile app and use it to study Newton's third law, of action-reaction forces. The teacher used an inquiry-based approach to prompt students to test towing capacity of the car. Students connected the car to different weights and used a structure of pulleys to investigate the behaviour of fixed and movable pulleys, as well as the forces involved. The goal of the activity is to motivate students to study physics and to facilitate learning. This article describes a pilot implementation of the educational product in a secondary school of Brazil. We used a qualitative approach to evaluate the implementation. Students answered a survey before and after the activities. They also delivered a report and answered questions about the physics involved. The teacher recorded his observations. The product and the strategy showed great potential: these students were more motivated and engaged in the classes and were able to learn the main concepts involved.